Targeting tubulin polymerization by novel 7-aryl-pyrroloquinolinones: Synthesis, biological activity and SARs - Bortolozzi, Roberta (Eur J Med Chem, 2017)
Earlier studies had confirmed that the 7-phenylpyrroloquinolinone (7-PPyQ) nucleus was an important scaffold for new chemotherapeutic drugs targeting microtubules. For wide-ranging SARs, a series of derivatives were synthesized through a robust procedure. For comparison with the reference 3-ethyl-7-PPyQ 31, the angular geometry and substituents at the 3 and 7 positions were varied to explore interactions inside the colchicine site of tubulin. Of the new compounds synthesized, potent cytotoxicity (low and sub-nanomolar GI(50) values) was observed with 21 and 24, both more potent than 31, in both leukemic and solid tumor cell lines. Neither compound 21 nor 24 induced significant cell death in normal human lymphocytes, suggesting that the compounds may be selectively active against cancer cells. In particular, 24 was a potent inducer of apoptosis in the A549 and HeLa cell lines. With both compounds, induction of apoptosis was associated with dissipation of the mitochondrial transmembrane potential and production of reactive oxygen species, indicating that cells treated with the compounds followed the intrinsic pathway of apoptosis. Moreover, immunoblot analysis revealed that compound 24 even at 50 nM reduced the expression of anti-apoptotic proteins such as Bcl-2 and Mcl-1. Finally, molecular docking studies of the newly synthesized compounds demonstrate that active pyrroloquinolinone derivatives strongly bind in the colchicine site of β-tubulin.